Psychotherapies for chronic kidney disease patients with hemodialysis: A systematic review of randomized control trials and quasi-experiments - Zahra, Zulfa; Effendy, Elmeida; Mawarpury, Marty; Marthoenis, Marthoenis; Jaya, Indra (Narra J, 2023)
Chronic kidney disease (CKD) patients, especially those with hemodialysis, frequently struggle with mental health issues like anxiety and depression. Psychotherapy has been known to treat psychological problems, but its effectiveness in managing CKD patients is still rarely scientifically proven. The aim of this study was to analyze the role of psychological treatments in improving the mental health of CKD patients with hemodialysis. We comprehensively reviewed the related studies published in PubMed, Google Scholar, ScienceDirect, and Clinical Key over the last ten years, up to June 7, 2023. A keyword combination was used in the search engine strategies, and all articles about CKD patients receiving hemodialysis and psychotherapy were included. Based on the eligibility criteria, 716 patients were included in 13 out of 18,830 studies in the final analysis. Psychological problem was complained by 399 CKD patients. The psychotherapy included cognitive behavioral therapy (reported in four studies, n=4), diaphragmatic breathing relaxation (n=1), meditation (n=1), hypnotherapy (n=1), Kidney Optimal Health Program (KOHP) (n=1), psychological intervention (n=1), murottal Al-Qur'an therapy (n=3), and spiritual therapy (n=1). These interventions were performed once to four times a week, for ten minutes to five hours during hemodialysis for two to ten weeks. Meditation and KOHP showed no significant improvement in anxiety and depression. The remaining psychotherapies significantly improved the quality of life by reducing anxiety and depression in hemodialysis patients and enhancing sleep quality, self-esteem, hopefulness, medication adherence, and physical condition. In conclusion, psychotherapy should be considered in an interdisciplinary team to treat CKD patients comprehensively. Further studies are still necessary to determine the efficacy of each psychological intervention in CKD patients with psychiatric problems.